CN / C / ROZIS heterojunction composite photocatalyst, preparation method and application thereof, and method for photocatalytic decomposition of water to produce hydrogen

CN122974347APending Publication Date: 2026-10-27SOUTHWEST FORESTRY UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611133025.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]本发明的目的在于克服现有ZnIn2S4基光催化剂光生载流子复合速率快、循环稳定性差、单一改性手段难以同时实现多性能协同提升的不足,提供一种CN/C/ROZIS异质结复合光催化剂及其制备方法和应用、光催化分解水制氢的方法,该CN/C/ROZIS异质结复合光催化剂通过Ru/O共掺杂调控能带结构,甘蔗渣生物炭强化电子传输,S型异质结实现空间电荷分离,兼具可见光响应范围宽、载流子分离效率高、氧化还原能力强和循环稳定性优异的特点

Benefits of technology

在上述技术方案中,本发明的CN/C/ROZIS异质结复合光催化剂通过Ru/O共掺杂改性硫化铟锌((Ru,O)-ZIS),搭配甘蔗渣基生物炭掺杂石墨相氮化碳(CN/C),原位构筑三维花瓣球形S型异质结复合光催化剂,依托多重协同作用,相较于传统单一光催化材料与二元复合材料具备多重突出优势。首先,本发明构建的S型异质结通过加速电荷转移、降低光生电荷的复合速率以及延长载流子寿命,显著促进了光生载流子的空间分离与迁移效率,从而促进光催化产氢速率的提升;同时甘蔗渣衍生生物炭具备优异导电网络,可作为高速电子传输通道,进一步加速界面电荷迁移,提升载流子利用效率。其次,Ru/O共掺杂可精准调控ZnIn2S4能带间隙,拓宽催化剂可见光响应范围,匹配λ>420nm的可见光光源,充分利用太阳光中占比最高的可见光波段,提升光能利用率,而三维花瓣球形分级结构具备更大比表面积,能够暴露充足的光催化活性位点,助力析氢反应高效进行。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974347A_ABST
    Figure CN122974347A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of photocatalytic materials, in particular to a CN / C / ROZIS heterojunction composite photocatalyst, a preparation method and application thereof, and a method for photocatalytic decomposition of water to produce hydrogen. The CN / C / ROZIS heterojunction composite photocatalyst is composed of ruthenium and oxygen co-doped indium zinc sulfide as a main body and biochar doped graphite phase carbon nitride as a loading phase. The CN / C / ROZIS heterojunction composite photocatalyst is spherical and has an S-type heterojunction composite structure. The mass fraction of the biochar doped graphite phase carbon nitride in the CN / C / ROZIS heterojunction composite photocatalyst is 0.02-0.50 wt.%. The CN / C / ROZIS heterojunction composite photocatalyst has the characteristics of a wide visible light response range, high carrier separation efficiency, strong redox capacity and excellent cycle stability by means of Ru / O co-doping for regulating the energy band structure, sugarcane residue biochar for strengthening electron transmission and an S-type heterojunction for realizing space charge separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photocatalytic materials technology, and in particular to a CN / C / ROZIS heterojunction composite photocatalyst, its preparation method and application, and a method for photocatalytic water splitting to produce hydrogen. Background Technology

[0002] Solar energy is a clean and pollution-free natural renewable energy source, and its efficient utilization is an important way to achieve sustainable social development. In recent years, researchers have developed various solar energy utilization technologies, mainly including photovoltaic power generation, photoelectrolysis hydrogen production, and solar thermal power generation. As an important branch of clean energy conversion, photocatalytic water splitting for hydrogen production can directly convert solar energy into hydrogen energy, effectively overcoming the inherent intermittency and instability of solar energy, and has great development prospects. However, currently, semiconductor photocatalysts still suffer from problems in practical applications such as insufficient light absorption capacity, slow photogenerated carrier migration rate, and excessively high recombination rate, which seriously restrict their large-scale application.

[0003] ZnIn₂S₄ (ZIS), a typical ternary metal sulfide semiconductor, possesses a suitable and tunable band structure and excellent visible light harvesting ability. Its good electron transport properties also make it easy to construct multi-component heterojunctions with other semiconductors, giving it broad application prospects in the field of photocatalytic hydrogen evolution. However, pure-phase ZIS still has significant shortcomings, mainly including rapid photogenerated carrier recombination rates, poor cycle stability, and limited monomeric catalytic activity, which severely restricts its practical application. To improve the carrier separation performance of semiconductor materials, elemental doping is the simplest and most commonly used modification method, effectively improving carrier mobility and suppressing photogenerated electron-hole pair recombination. However, single-element doping modification methods have limited optimization potential and usually cannot simultaneously achieve multiple objectives such as broadening the photoresponse range, optimizing interfacial charge transport, and improving structural stability; the overall modification effect still faces significant bottlenecks.

[0004] Among numerous biochar precursor materials, bagasse stands out due to its unique microstructure. Its inherent fibrous network structure facilitates the retention of a rich porous framework during carbonization, and its abundant oxygen-containing functional groups on the surface provide numerous anchoring sites for active components. Converting bagasse into biochar for modifying photocatalysts not only addresses the environmental burden caused by waste accumulation but also aligns with the principles of green chemistry. Therefore, utilizing bagasse to prepare biochar can further suppress the rapid recombination of photogenerated charges, broaden the photoresponse range, and simultaneously achieve the resource-based transformation of waste.

[0005] No literature has yet systematically disclosed a technical scheme for combining sugarcane bagasse-derived biochar doped with g-C3N4 and Ru and O co-doped with ZnIn2S4, and constructing an S-type heterojunction in situ via a one-step hydrothermal method for photocatalytic hydrogen production. Nor has it revealed the intrinsic mechanism by which the three synergistically regulate carrier transport. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of existing ZnIn2S4-based photocatalysts, such as fast photogenerated carrier recombination rate, poor cycle stability, and difficulty in achieving synergistic improvement of multiple performance characteristics with a single modification method. This invention provides a CN / C / ROZIS heterojunction composite photocatalyst, its preparation method, and its applications, as well as a method for photocatalytic water splitting to produce hydrogen. This CN / C / ROZIS heterojunction composite photocatalyst utilizes Ru / O co-doping to regulate the band structure, sugarcane bagasse biochar to enhance electron transport, and an S-shaped heterojunction to achieve space charge separation. It features a wide visible light response range, high carrier separation efficiency, strong redox ability, and excellent cycle stability. Furthermore, the preparation method of this CN / C / ROZIS heterojunction composite photocatalyst employs an in-situ integrated process: one-step calcination to prepare biochar-doped g-C3N4, and one-step hydrothermal in-situ construction of the heterojunction. The process is simple, the conditions are mild, the interfacial bonding is strong, and it achieves high-value utilization of sugarcane bagasse waste, making it easy to scale up for production. This CN / C / ROZIS heterojunction composite photocatalyst can achieve efficient and stable hydrogen production under mild conditions in visible light photocatalytic water splitting for hydrogen production, showing promising prospects for industrial application.

[0007] To achieve the above objectives, in a first aspect, the present invention provides a CN / C / ROZIS heterojunction composite photocatalyst, wherein the CN / C / ROZIS heterojunction composite photocatalyst is composed of ruthenium- and oxygen-doped indium zinc sulfide as the main body and biochar-doped graphitic carbon nitride as the supporting phase; wherein... The CN / C / ROZIS heterojunction composite photocatalyst is spherical and has an S-type heterojunction composite structure; The biochar-doped graphitic carbon nitride in the CN / C / ROZIS heterojunction composite photocatalyst has a mass fraction of 0.02~0.50 wt.%.

[0008] Preferably, the ruthenium and oxygen co-doped indium zinc sulfide is self-assembled from two-dimensional nanosheets, exhibiting a three-dimensional petal-shaped spherical microstructure.

[0009] Preferably, biochar-doped graphitic carbon nitride nanoparticles are dispersed and loaded on the surface and interlamellar gaps of a ruthenium- and oxygen-doped indium zinc sulfide three-dimensional petal-shaped spherical microstructure.

[0010] Preferably, the biochar is made from sugarcane bagasse.

[0011] Secondly, the present invention provides a method for preparing a CN / C / ROZIS heterojunction composite photocatalyst as described in the present invention, the preparation method comprising: 1) In the presence of an alkaline solution, nitrogen-containing precursors and sugarcane bagasse are mixed, dried, and calcined to obtain biochar-doped g-C3N4, i.e. CN / C; 2) In the presence of a solvent, CN / C, zinc salt, indium salt, sulfur source, oxygen source and ruthenium salt from step 1) are mixed, subjected to hydrothermal reaction, cooled, washed and dried to obtain CN / C / ROZIS heterojunction composite photocatalyst.

[0012] Preferably, in step 1), the alkaline solution is an aqueous solution of potassium hydroxide and / or an aqueous solution of sodium hydroxide.

[0013] Preferably, the concentration of the alkaline solution is 2.5~10 g / L.

[0014] Preferably, the nitrogen-containing precursor is selected from one or more of melamine, dicyandiamide, urea, and thiourea.

[0015] Preferably, the mass ratio of the nitrogen-containing precursor to bagasse is 1:0.0020~0.0030.

[0016] Preferably, in step 1), the mixing conditions include: ultrasonication for 0.5 to 2 hours at a power of 200 to 400 W.

[0017] Preferably, the drying conditions include a temperature of 60-80°C and a time of 8-16 hours.

[0018] Preferably, the calcination conditions include: a temperature of 500~600℃ and a time of 1~3h.

[0019] Preferably, in step 2), the solvent is deionized water and / or distilled water.

[0020] Preferably, the zinc salt is selected from one or more of zinc chloride, zinc acetate, and zinc acetate.

[0021] Preferably, the indium salt is indium trichloride and / or indium nitrate.

[0022] Preferably, the sulfur source is selected from one or more of thioacetamide, thiourea, and L-cysteine.

[0023] Preferably, the oxygen source is selected from one or more of polyvinylpyrrolidone, ethylene glycol, citric acid, and Pluronic F127.

[0024] Preferably, the ruthenium salt is selected from one or more of ruthenium trichloride hydrate, ruthenium acetate, and ruthenium acetylacetonate.

[0025] Preferably, the molar ratio of the zinc salt, indium salt, sulfur source, oxygen source and ruthenium salt is 1:2:8:0.002~0.004:0.15~0.25; wherein the zinc salt is calculated by the amount of zinc, the indium salt by the amount of indium, and the ruthenium salt by the amount of ruthenium.

[0026] Preferably, the ratio of zinc salt to CN / C is 1 mmol: 0.0001~0.002 g, wherein the zinc salt is in the form of Zn. 2+ count.

[0027] Preferably, in step 2), the conditions for the hydrothermal reaction include: a temperature of 160~200℃ and a time of 12~24h.

[0028] Preferably, the washing conditions include washing with deionized water and anhydrous ethanol 3 to 5 times each.

[0029] Preferably, the drying conditions include: under vacuum conditions, a temperature of 70~90°C, and a time of 8~16 hours.

[0030] Thirdly, the present invention provides an application of the CN / C / ROZIS heterojunction composite photocatalyst as described in the present invention in visible light catalytic water splitting for hydrogen production.

[0031] Fourthly, the present invention provides a method for photocatalytic water splitting to produce hydrogen, the method comprising: dispersing a photocatalyst in a triethanolamine aqueous solution with a volume fraction of 15-25%, adding an alkaline substance to adjust the system to alkalinity, purging an inert gas to remove air from the reaction system, and then carrying out a photocatalytic hydrogen production reaction under visible light irradiation; The photocatalyst is the CN / C / ROZIS heterojunction composite photocatalyst described in this invention.

[0032] Preferably, 80-120 mg of photocatalyst and 1-2 g of alkaline substance are added to every 20 mL of triethanolamine aqueous solution.

[0033] Preferably, the alkaline substance is sodium hydroxide and / or potassium hydroxide.

[0034] Preferably, the inert gas ventilation time is 20-40 minutes.

[0035] Preferably, the reaction temperature of the photocatalytic hydrogen production reaction is 15~30℃.

[0036] Preferably, the wavelength of the visible light satisfies λ>420 nm.

[0037] Beneficial effects of the invention In the above technical solution, the CN / C / ROZIS heterojunction composite photocatalyst of the present invention is prepared by modifying indium zinc sulfide via Ru / O co-doping ((Ru,O)-ZIS), matching with bagasse-derived biochar-doped graphitic carbon nitride (CN / C), to in-situ construct a three-dimensional petal-spherical S-scheme heterojunction composite photocatalyst. Relying on multiple synergistic effects, it has multiple prominent advantages over traditional single photocatalytic materials and binary composite materials. Firstly, the S-scheme heterojunction constructed by the present invention significantly promotes the spatial separation and migration efficiency of photogenerated charge carriers by accelerating charge transfer, reducing the recombination rate of photogenerated charges and prolonging the carrier lifetime, thereby promoting the improvement of the photocatalytic hydrogen production rate; at the same time, the bagasse-derived biochar has an excellent conductive network, which can act as a high-speed electron transmission channel to further accelerate interfacial charge migration and improve carrier utilization efficiency. Secondly, Ru / O co-doping can precisely regulate the band gap of ZnIn₂S₄, broaden the visible light response range of the catalyst, match the visible light source with λ>420 nm, make full use of the visible light band that accounts for the highest proportion in sunlight, and improve the light energy utilization rate. The three-dimensional petal-spherical hierarchical structure has a larger specific surface area, which can expose sufficient photocatalytic active sites to facilitate the efficient progress of the hydrogen evolution reaction.

[0038] Meanwhile, the preparation method of the CN / C / ROZIS heterojunction composite photocatalyst of the present invention adopts a preparation process of first calcining to prepare biochar-doped graphitic carbon nitride (CN / C), and then performing one-step hydrothermal in-situ recombination. The process is simple and mild, no complex post-treatment procedures are required, the raw materials have a wide optional range and strong adaptability, and agricultural waste bagasse is used as the carbon source, which realizes the resource utilization of solid waste, is environmentally friendly and reduces the preparation cost; PVP added in the hydrothermal process can precisely regulate the microscopic morphology, ensure the close fitting of the heterojunction interface, and further enhance the charge transmission efficiency.

[0039] In addition, the supporting visible light water splitting hydrogen production system of the present invention adjusts the pH of the reaction system through an alkaline reagent. On the one hand, it inhibits the photocorrosion phenomenon of the ZnIn₂S₄ semiconductor and improves the recycling stability of the catalyst; on the other hand, it enhances the hole trapping capacity of the hole sacrificial agent (triethanolamine). The whole reaction is carried out under mild conditions of visible light at room temperature, with low energy consumption and simple operation, and the CN / C / ROZIS heterojunction composite photocatalyst of the present invention has excellent hydrogen production activity and cycling stability, and has extremely high practical application value.

[0040] Other features and advantages of the present invention will be described in detail in the subsequent section of Detailed Description. Brief Description of the Drawings

[0041] The accompanying drawings are provided to further understand the present invention, constitute a part of the specification, and together with the following detailed description, serve to explain the present invention without constituting a limitation to the present invention. In the accompanying drawings: Figure 1Images (a)-(c) are scanning electron microscope (SEM) images and magnified SEM images of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3; (d) is an SEM image of biochar-doped g-C3N4 prepared in Comparative Example 3; (e) is a transmission electron microscope (TEM) image of biochar-doped g-C3N4 prepared in Comparative Example 3; (f) is a high-resolution transmission electron microscope (HRTEM) image of biochar-doped g-C3N4 prepared in Comparative Example 3; (g) is a TEM image of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3; (h) is an HRTEM image of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3; and (i) is an elemental mapping diagram of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3. Figure 2 The X-ray diffraction (XRD) spectra of the CN / C / ROZIS heterojunction composite photocatalysts prepared in Examples 1-5 and the products prepared in Comparative Examples 1-3 are shown. Figure 3 Fourier transform infrared (FT-IR) spectra of the CN / C / ROZIS heterojunction composite photocatalysts prepared in Examples 1-5 and the products prepared in Comparative Examples 1-3. Figure 4 (a) shows the UV-Vis spectra of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 and the products prepared in Comparative Examples 1-3; (b) shows the Tauc diagrams of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 and the products prepared in Comparative Examples 1-3. Figure 5 (a) is the Mott-Schottky diagram of the product prepared in Comparative Example 2; (b) is the Mott-Schottky diagram of the product prepared in Comparative Example 3; (c) is the Mott-Schottky diagram of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3. Figure 6 (a) shows the photoluminescence (PL) spectra of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 and the products prepared in Comparative Examples 1-3; (b) shows the transient fluorescence (TRPL) spectra of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 and the products prepared in Comparative Examples 1-3; (c) shows the electrochemical impedance spectroscopy (EIS) spectra of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 and the products prepared in Comparative Examples 1-3; (d) shows the transient photocurrent response of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 and the products prepared in Comparative Examples 1-3. Figure 7(a) shows the photocatalytic hydrogen production performance of the CN / C / ROZIS heterojunction composite photocatalysts prepared in Examples 1-5 and the products prepared in Comparative Examples 1-2 within 4 hours; (b) shows the H2 production rate of the CN / C / ROZIS heterojunction composite photocatalysts prepared in Examples 1-5 and the products prepared in Comparative Examples 1-2; (c) shows the apparent quantum efficiency of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3; and (d) shows the cycle stability test of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 and the products prepared in Comparative Examples 1-2. Figure 8 (a) shows the EPR signal of DMPO-·OH of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 and the products prepared in Comparative Examples 2-3; (b) shows the DMPO-·O2 signal of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 and the products prepared in Comparative Examples 2-3. - EPR signal; Figure 9 The band structure diagram of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 is shown. Figure 10 This is a diagram illustrating the photocatalytic hydrogen production mechanism of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3. Detailed Implementation

[0042] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.

[0043] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0044] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0045] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0046] In a first aspect, the present invention provides a CN / C / ROZIS heterojunction composite photocatalyst, wherein the CN / C / ROZIS heterojunction composite photocatalyst is composed of ruthenium- and oxygen-doped indium zinc sulfide ((Ru,O)-ZIS) as the main body and biochar-doped graphitic carbon nitride (CN / C) as the supporting phase; wherein... The CN / C / ROZIS heterojunction composite photocatalyst is spherical and has an S-type heterojunction composite structure. The S-type heterojunction band arrangement can simultaneously retain a strong redox potential.

[0047] The biochar-doped graphitic carbon nitride in the CN / C / ROZIS heterojunction composite photocatalyst has a mass fraction of 0.02~0.50 wt.%. If the CN / C content is too low, a sufficient heterojunction interface cannot be formed, and the charge separation effect is not obvious; if the content is too high, it will block the ROZIS active sites and hinder light absorption and charge transport. Within the scope of this invention, it can ensure the formation of an effective S-type heterojunction while avoiding the inhibitory effect of excessive CN / C on the reaction, thereby maximizing the hydrogen production performance.

[0048] The CN / C / ROZIS heterojunction composite photocatalyst of this invention is constructed in situ using Ru / O co-doped modified indium zinc sulfide ((Ru,O)-ZIS) and sugarcane bagasse-based biochar-doped graphitic carbon nitride (CN / C). This process creates a three-dimensional petal-shaped spherical S-type heterojunction composite photocatalyst. Due to the suitable band gap, excellent chemical stability, and unique two-dimensional layered structure of graphitic carbon nitride (g-C3N4), its conduction and valence band positions form an alternating band arrangement with ZIS, which is beneficial for constructing a stable S-type heterojunction at the interface, further promoting the efficient migration and separation of photogenerated carriers. Introducing biochar into the photocatalytic system can also enhance photocatalytic performance to some extent. The S-type heterostructure consists of an oxidized photocatalyst and a reduced photocatalyst. Due to the difference in conduction band positions and Fermi levels between the two, a built-in electric field is formed at the interface. This electric field not only drives the spatial separation of photogenerated charges but also maintains a high redox potential, thereby endowing the composite material with stronger redox capabilities. Therefore, constructing an S-type heterojunction for ZIS after elemental doping modification can compensate for the performance shortcomings of single doping modification, realize the combined advantages of modification methods, maximize the optimization of charge separation efficiency, and significantly improve the overall photocatalytic performance.

[0049] The CN / C / ROZIS heterojunction composite photocatalyst of this invention, relying on multiple synergistic effects, possesses several outstanding advantages compared to traditional single photocatalytic materials and binary composite materials. Firstly, the S-shaped heterojunction constructed in this invention significantly promotes the spatial separation and migration efficiency of photogenerated carriers by accelerating charge transfer, reducing the recombination rate of photogenerated charges, and extending carrier lifetime, thereby enhancing the photocatalytic hydrogen production rate. Simultaneously, the bagasse-derived biochar possesses an excellent conductive network, serving as a high-speed electron transport channel to further accelerate interfacial charge migration and improve carrier utilization efficiency. Secondly, Ru / O co-doping allows for precise control of the ZnIn2S4 band gap, broadening the catalyst's visible light response range and matching visible light sources with λ>420nm, fully utilizing the most prevalent visible light band in sunlight to improve light energy utilization. Furthermore, the three-dimensional petal-shaped spherical hierarchical structure has a larger specific surface area, exposing sufficient photocatalytic active sites to facilitate efficient hydrogen evolution reaction.

[0050] In this invention, the ruthenium and oxygen co-doped indium zinc sulfide is self-assembled from two-dimensional nanosheets, exhibiting a three-dimensional petal-shaped spherical microstructure with a high specific surface area. The high specific surface area provides a large number of reactive sites, and the S-type heterojunction achieves efficient spatial separation of charges. The two work together to enhance photocatalytic activity.

[0051] In this invention, biochar-doped graphitic carbon nitride nanoparticles are dispersed and loaded on the surface and interlamellar gaps of a ruthenium- and oxygen-doped indium zinc sulfide three-dimensional petal-shaped spherical microstructure.

[0052] In this invention, the biochar is made from sugarcane bagasse, which is an agricultural waste rich in fibrous structure. After carbonization, it can form porous biochar, which has both cost and environmental advantages, realizing the resource utilization of waste. The graphite-like structure of biochar can serve as a fast electron transfer channel, accelerating charge transport.

[0053] Secondly, the present invention provides a method for preparing a CN / C / ROZIS heterojunction composite photocatalyst as described in the present invention, the preparation method comprising: 1) In the presence of an alkaline solution, nitrogen-containing precursors and sugarcane bagasse are mixed, dried, and calcined to obtain biochar-doped g-C3N4, i.e. CN / C; 2) In the presence of a solvent, CN / C, zinc salt, indium salt, sulfur source, oxygen source and ruthenium salt from step 1) are mixed, subjected to hydrothermal reaction, cooled, washed and dried to obtain CN / C / ROZIS heterojunction composite photocatalyst.

[0054] The method for preparing the CN / C / ROZIS heterojunction composite photocatalyst of this invention adopts a process of first calcining biochar-doped graphitic carbon nitride (CN / C) and then performing hydrothermal in-situ composite in one step. The process is simple and mild, requires no complicated post-processing steps, has a wide range of raw material options and strong adaptability, and uses agricultural waste sugarcane bagasse as a carbon source to realize the resource utilization of solid waste, which is green and environmentally friendly and reduces the preparation cost. The PVP added during the hydrothermal process can precisely control the microstructure, ensure tight adhesion of the heterojunction interface, and further enhance the charge transport efficiency.

[0055] In this invention, in step 1), the alkaline solution first provides an alkaline environment for the preparation of CN / C, promoting the condensation reaction of the nitrogen-containing precursor to generate g-C3N4; secondly, it causes the bagasse to swell, which is beneficial for the biochar to be uniformly incorporated into the g-C3N4 framework during calcination; finally, it moderately etches the g-C3N4 during calcination, introducing a porous structure and increasing the specific surface area. Therefore, a strong alkali is preferred, such as an aqueous solution of potassium hydroxide and / or an aqueous solution of sodium hydroxide; the concentration of the alkaline solution is 2.5~10 g / L. Within this concentration range, the g-C3N4 condensation reaction is complete, which can both ensure the crystallinity of carbon nitride and control the condensation reaction rate to prevent it from being too fast.

[0056] In this invention, in step 1), the nitrogen-containing precursor can provide both carbon and nitrogen sources that can generate g-C3N4 at high temperatures, such as one or more selected from melamine, dicyandiamide, urea and thiourea, among which melamine has high thermal stability and stable yield, making it the optimal choice.

[0057] In this invention, in step 1), the mass ratio of the nitrogen-containing precursor to bagasse is 1:0.0020~0.0030.

[0058] In this invention, in step 1), in order to uniformly disperse the sugarcane bagasse and nitrogen-containing precursor, avoid agglomeration, and ensure uniform doping of the biochar in g-C3N4 after calcination, the mixing conditions include: ultrasonication for 0.5 to 2 hours at a power of 200 to 400 W.

[0059] In this invention, the drying conditions in step 1) include: a temperature of 60~80℃ and a time of 8~16h.

[0060] In this invention, the calcination conditions in step 1) include a temperature of 500~600℃ and a time of 1~3h, which can ensure the complete pyrolysis of the precursor while avoiding decomposition due to excessively high temperature.

[0061] In this invention, in step 2), the solvent can ensure the full dissolution of the reactants, control the crystal morphology, and achieve in-situ recombination of CN / C with (Ru,O)-ZIS. For example, it can be deionized water and / or distilled water.

[0062] In this invention, in step 2), in order to ensure the nucleation and growth of ZnIn2S4 crystals and form a uniform petal-shaped spherical microstructure, the zinc salt is selected from one or more of zinc chloride, zinc acetate, and zinc acetate; the indium salt is indium trichloride and / or indium nitrate; the sulfur source is selected from one or more of thioacetamide, thiourea, and L-cysteine; and the ruthenium salt is selected from one or more of ruthenium trichloride hydrate, ruthenium acetate, and ruthenium acetylacetone.

[0063] In this invention, in step 2), the oxygen source is a water-soluble oxygen-containing polymeric surfactant or an oxygen-containing small molecule, which has the dual function of supplying oxygen and regulating crystal morphology. It can be selected from one or more of polyvinylpyrrolidone, ethylene glycol, citric acid and Pluronic F127.

[0064] In this invention, in step 2), the molar ratio of zinc salt, indium salt, sulfur source, oxygen source, and ruthenium salt is 1:2:8:0.002~0.004:0.15~0.25; wherein, zinc salt is calculated based on the amount of zinc, indium salt on the amount of indium, ruthenium salt on the amount of ruthenium, polyvinylpyrrolidone on the amount of pyrrolidone monomer units, and the remaining oxygen sources are calculated based on the molar amount of equivalent active oxygen-containing groups. Pluronic F127 is calculated based on the total molar amount of intramolecular ethylene oxide (EO) units, ethylene glycol is calculated based on the molar amount of hydroxyl groups in the molecule, and citric acid is calculated based on the molar amount of total active oxygen-containing sites of carboxyl and hydroxyl groups in the molecule. When multiple oxygen sources are used in combination, the total molar amount of effective oxygen-containing groups after conversion of each oxygen source is controlled at 0.002~0.004 parts.

[0065] Zinc and indium elements strictly adhere to the Zn:In stoichiometric ratio of Zn:In = 1:2 to ensure the formation of pure hexagonal ZnIn2S4. The amount of sulfur source used is twice the theoretical stoichiometric value to compensate for the loss of sulfur components during hydrothermal reaction and to avoid the formation of sulfur-deficient impurity phases. The effective molar amount of oxygen-containing groups after conversion is limited to 0.002-0.004 parts. On the one hand, it can selectively adsorb specific crystal faces, inducing the self-assembly of two-dimensional nanosheets to form a complete and uniform petal-shaped spherical microstructure. On the other hand, hydrothermal decomposition provides oxygen atoms to achieve lattice oxygen doping and narrow the catalyst band gap. If the converted amount of oxygen source is lower than this range, the ability to control the crystal face orientation is insufficient and the amount of oxygen doping is too low, which easily leads to the problems of sheet aggregation and aggravated recombination of photogenerated carriers. If the converted amount of oxygen source is higher than this range, the polymeric oxygen source will excessively encapsulate the crystal grains and block the active pores. Excessive citric acid will strongly complex zinc and indium metal ions, destroy the raw material stoichiometric ratio, and generate hydroxide impurity phases. The ruthenium salt is present in amounts of 0.15–0.25 parts by weight (calculated as ruthenium). A small amount of Ru can replace In sites in the crystal lattice to construct charge traps, effectively suppressing photogenerated electron-hole recombination. However, excessive ruthenium content can lead to agglomeration on the catalyst surface, obscuring light-absorbing active sites and reducing photocatalytic hydrogen production performance. Within this ratio range, a catalytic material with a pure product phase, regular petal-like spherical morphology, uniform oxygen doping, no Ru agglomeration, and abundant active sites can be simultaneously achieved, resulting in optimal photocatalytic hydrogen production performance.

[0066] In a preferred embodiment of the present invention, polyvinylpyrrolidone is selected as the oxygen source, and the molar amount of pyrrolidone monomer unit is directly controlled at 0.002~0.004 parts, which makes the feeding and metering simple and achieves the best morphology control and oxygen doping effect.

[0067] In this invention, in step 2), the ratio of zinc salt to CN / C is 1 mmol: 0.0001~0.002 g, wherein the zinc salt is in the form of Zn. 2+ count.

[0068] In this invention, in step 2), the conditions for the hydrothermal reaction include: a temperature of 160~200℃ and a time of 12~24h. This temperature range can ensure that the crystals grow fully and form a complete petal-like structure, avoiding incomplete crystallization due to excessively low temperatures and agglomeration due to excessively high temperatures.

[0069] In this invention, step 2) includes washing with deionized water and anhydrous ethanol 3 to 5 times each.

[0070] In this invention, the drying conditions in step 2) include: under vacuum conditions, a temperature of 70~90℃, and a time of 8~16h.

[0071] Thirdly, the present invention provides an application of the CN / C / ROZIS heterojunction composite photocatalyst as described in the present invention in visible light catalytic water splitting for hydrogen production.

[0072] Fourthly, the present invention provides a method for photocatalytic water splitting to produce hydrogen, the method comprising: dispersing a photocatalyst in a triethanolamine aqueous solution with a volume fraction of 15-25%, adding an alkaline substance to adjust the system to alkalinity, purging an inert gas to remove air from the reaction system, and then carrying out a photocatalytic hydrogen production reaction under visible light irradiation; The photocatalyst is the CN / C / ROZIS heterojunction composite photocatalyst described in this invention.

[0073] The visible light water splitting hydrogen production system of this invention uses alkaline reagents to regulate the pH of the reaction system. This suppresses photocorrosion of the ZnIn2S4 semiconductor and improves the stability of the catalyst during recycling. It also enhances the hole-trapping ability of the hole sacrificial agent. The entire reaction takes place under mild visible light conditions at room temperature, resulting in low energy consumption and simple operation. Furthermore, the CN / C / ROZIS heterojunction composite photocatalyst of this invention exhibits excellent hydrogen production activity and cycling stability, making it highly valuable for practical applications.

[0074] In this invention, 80-120 mg of photocatalyst and 1-2 g of alkaline substance are added to every 20 mL of triethanolamine aqueous solution. The addition of alkaline substance can improve the stability of photocatalyst, extend its service life, and increase the hydrogen production rate.

[0075] In this invention, the alkaline substance is sodium hydroxide and / or potassium hydroxide.

[0076] In this invention, the inert gas is ventilated for 20-40 minutes to ensure that the hydrogen evolution reaction takes place in an oxygen-free environment, thereby improving the purity and yield of hydrogen.

[0077] In this invention, the reaction temperature of the photocatalytic hydrogen production reaction is 15~30℃, which is a mild room temperature condition to avoid catalyst deactivation or triethanolamine (TEOA) decomposition caused by high temperature.

[0078] In this invention, the wavelength of the visible light satisfies λ>420 nm.

[0079] In this invention, the room temperature is 15~30℃.

[0080] The present invention will be described in detail below through examples, but the scope of protection of the present invention is not limited thereto. In the following examples, the drugs and pharmaceuticals are all conventional commercially available products.

[0081] Example 1 (1) Dissolve 0.25 g potassium hydroxide (KOH) in deionized water, add 50 g melamine and 0.125 g sugarcane bagasse, sonicate for 1 h, dry at 70 °C for 12 h, and then calcine the resulting solid at 550 °C for 2 h to obtain biochar-doped g-C3N4, denoted as CN / C.

[0082] (2) 1 mmol ZnCl2, 2 mmol InCl3·4H2O, 8 mmol thioacetamide (TAA), 0.003 mmol polyvinylpyrrolidone (PVP), 0.20 mmol RuCl3·xH2O and 0.0001 g CN / C obtained in step (1) were added to 40 mL of deionized water and stirred until completely dissolved. The solution was then transferred to a 100 mL hydrothermal reactor and reacted at 180 °C for 18 h. After natural cooling, the solution was washed 3 to 5 times with deionized water and ethanol, and dried at 80 °C for 12 h to obtain the CN / C / ROZIS heterojunction composite photocatalyst, denoted as CN / C / ROZIS1, wherein the mass fraction of CN / C was 0.024 wt.%.

[0083] Example 2 The process was carried out in accordance with Example 1, except that “0.0001 g of CN / C obtained in step (1)” in step (2) was replaced with “0.0005 g of CN / C obtained in step (1)”, and other conditions remained unchanged, to obtain CN / C / ROZIS heterojunction composite photocatalyst, denoted as CN / C / ROZIS2, wherein the mass fraction of CN / C was 0.119 wt.%.

[0084] Example 3 The process was carried out in accordance with Example 1, except that “0.0001 g of CN / C obtained in step (1)” in step (2) was replaced with “0.001 g of CN / C obtained in step (1)”, while other conditions remained unchanged, and CN / C / ROZIS heterojunction composite photocatalyst was obtained, denoted as CN / C / ROZIS3, wherein the mass fraction of CN / C was 0.237 wt.%.

[0085] Example 4 The process was carried out in accordance with Example 1, except that “0.0001 g of CN / C obtained in step (1)” in step (2) was replaced with “0.0015 g of CN / C obtained in step (1)”, and other conditions remained unchanged, to obtain CN / C / ROZIS heterojunction composite photocatalyst, denoted as CN / C / ROZIS4, wherein the mass fraction of CN / C was 0.356 wt.%.

[0086] Example 5 The process was carried out in accordance with Example 1, except that “0.0001 g of CN / C obtained in step (1)” in step (2) was replaced with “0.002 g of CN / C obtained in step (1)”, while other conditions remained unchanged, and CN / C / ROZIS heterojunction composite photocatalyst was obtained, denoted as CN / C / ROZIS5, wherein the mass fraction of CN / C was 0.473 wt.%.

[0087] Comparative Example 1 1 mmol ZnCl2, 2 mmol InCl3·4H2O and 8 mmol TAA were added to 40 mL of deionized water, stirred and dissolved, and then transferred to a 100 mL hydrothermal reactor. The reaction was carried out at 180 °C for 18 h. After natural cooling, the mixture was washed 3-5 times each with deionized water and ethanol, and dried at 80 °C for 12 h to obtain pure ZnIn2S4, denoted as ZIS.

[0088] Comparative Example 2 1 mmol ZnCl2, 2 mmol InCl3·4H2O, 8 mmol TAA, 0.003 mmol PVP, and 0.20 mmol RuCl3·xH2O were added to 40 mL of deionized water, stirred until dissolved, and then transferred to a 100 mL hydrothermal reactor. The reaction was carried out at 180 °C for 18 h. After natural cooling, the mixture was washed 3–5 times each with deionized water and ethanol, and dried at 80 °C for 12 h to obtain Ru / O co-doped ZnIn2S4, denoted as (Ru,O)-ZIS.

[0089] Comparative Example 3 Dissolve 0.25 g potassium hydroxide (KOH) in deionized water, add 50 g melamine and 0.125 g sugarcane bagasse, sonicate for 1 h, dry at 70 °C for 12 h, and then calcine the resulting solid at 550 °C for 2 h to obtain biochar-doped g-C3N4, denoted as CN / C.

[0090] Application Example 1 100 mg of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Examples 1-5 and the product prepared in Comparative Examples 1-2 were weighed separately and dispersed independently in 20 mL of triethanolamine (TEOA) aqueous solution (20% by volume), and 1.5 g of sodium hydroxide (NaOH) was added. The mixture was placed in a 250 mL quartz photoreactor, and nitrogen gas was introduced for 30 minutes to purge air. The photocatalytic reaction was carried out under visible light (λ>420 nm) irradiation, and the reaction temperature was controlled at 25 °C by circulating water. The hydrogen production was sampled and analyzed every 30 minutes using gas chromatography (FULI, GC 9790plus), and the results are as follows. Figure 7 (a)-(b) and Table 1 are shown.

[0091] Table 1 Depend on Figure 7 As shown in (a), the amount of hydrogen produced by the CN / C / ROZIS heterojunction composite photocatalysts prepared in Examples 1-5 and the products prepared in Comparative Examples 1-2 under visible light irradiation is linearly related to the test time, indicating that the CN / C / ROZIS heterojunction composite photocatalysts prepared in Examples 1-5 and the products prepared in Comparative Examples 1-2 can continuously react with water to produce hydrogen under visible light.

[0092] Depend on Figure 7 As shown in (b), compared with the product (Ru,O)-ZIS prepared in Comparative Example 2 and the CN / C / ROZIS heterojunction composite photocatalyst prepared in Examples 1-5, the product ZIS prepared in Comparative Example 1 exhibited the slowest hydrogen production rate, indicating that Ru and O atom doping and CN / C loading can enhance the photocatalytic activity of ZIS. Furthermore, as the CN / C content gradually increased, the hydrogen production rate of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Examples 1-3 increased, achieving a maximum H2 generation rate of 9.786 mmol·g at a CN / C loading of 0.001 g. -1 ·h -1 The H2 generation rate of the pure ZIS product obtained in Comparative Example 1 was 0.128 mmol·g. -1 ·h -1 The rate of hydrogen generation was 76.3 times that of the original CN / C. However, as the loading of CN / C continued to increase, the hydrogen generation rate of the CN / C / ROZIS heterojunction composite photocatalysts prepared in Examples 4-5 began to decrease, because the addition of excessive CN / C hindered the absorption of visible light by ZIS.

[0093] Application Example 2 Using the CN / C / ROZIS3 heterojunction composite photocatalyst prepared in Example 3 as the research object, while keeping other conditions unchanged in Application Example 1, bandpass filters of 400, 420, 450, 500, and 550 nm were used to filter the xenon lamp source to obtain monochromatic visible light. The hydrogen production and apparent quantum efficiency at each wavelength were measured over 4 hours. The results are as follows: Figure 5 (c) and Table 2 are shown.

[0094] The apparent quantum efficiency (AQE) is calculated according to formula (1): Where, N H2 Indicates the number of hydrogen molecules produced; N p Indicates the number of incident photons; NA This represents the molar constant, with a value of 6.02 × 10⁻⁶. 23 ; R (mol) represents H2 production; E (W) represents luminous power; λ (nm) represents wavelength; h represents Planck's constant (J·s), with a value of 6.626 × 10⁻⁶. -34 ; c (m / s) represents the speed of light, with a value of 3 × 10⁻⁶. 8 .

[0095] Table 2 Depend on Figure 7 (c) As can be seen from the content, under monochromatic light irradiation at 400, 420, 450, 500 and 550 nm, the CN / C / ROZIS heterojunction composite photocatalyst CN / C / ROZIS3 prepared in Example 3 has the highest apparent quantum efficiency at 400 nm, reaching 19.07%.

[0096] Application Example 3 Cyclic stability test: Using the CN / C / ROZIS heterojunction composite photocatalyst CN / C / ROZIS3 prepared in Example 3 and the products obtained in Comparative Examples 1-2 as research objects, four rounds of cyclic photocatalytic hydrogen production experiments were conducted, with each round lasting 4 hours. After each round of reaction, the catalyst was recovered by centrifugation, washed twice each with deionized water and anhydrous ethanol, and then vacuum dried at 80°C before being reused in the next round of reaction. The test results are as follows: Figure 7 As shown in (d).

[0097] Depend on Figure 7 As can be seen from (d), after four rounds of cyclic testing, the CN / C / ROZIS heterojunction composite photocatalyst CN / C / ROZIS3 prepared in Example 3 still maintains 86.24% of its original photocatalytic performance, indicating that the CN / C / ROZIS heterojunction composite photocatalyst prepared in this invention has good reusability.

[0098] Detection Example 1 The morphology and microstructure of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 and the biochar-doped g-C3N4 prepared in Comparative Example 3 were characterized using scanning electron microscopy (SEM), transmission electron microscopy (TEM), and high-resolution transmission electron microscopy (HRTEM). The results are as follows: Figure 1 As shown.

[0099] Depend on Figure 1(a) SEM images of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 show that the CN / C / ROZIS heterojunction composite photocatalyst still maintains a spherical structure; a magnified view of its portion... Figure 1 (b) shows that the petal-shaped nanosheets are surrounded by uniformly distributed small spherical particles. These particles are uniformly dispersed on the surface and in the gaps of the nanosheet structure, indicating that CN / C was successfully loaded onto (Ru,O)-ZIS; Figure 1 (c) It can be seen that the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 exhibits a uniform spherical morphology. The uniform spherical structure can improve the light absorption efficiency, and the rough texture on the surface can further improve the light capture rate.

[0100] Depend on Figure 1 (d) It can be seen that the biochar-doped g-C3N4 in Comparative Example 3 exhibits an aggregated morphology composed of irregular nanoparticles and blocky fragments. This aggregated morphology has a dual impact on photocatalytic performance. On the one hand, nanoparticles increase the number of surface active sites and contribute to light absorption; on the other hand, severe aggregation and the presence of blocky fragments reduce the effective specific surface area, prolong the path for charge carriers to migrate to surface reaction sites, and may also obscure some active centers, ultimately exacerbating charge recombination.

[0101] exist Figure 1 (e) In the TEM image of biochar-doped g-C3N4 of Comparative Example 3, the biochar-doped g-C3N4 exhibits a disordered aggregate morphology composed of small and irregular nanoparticles. Further observation... Figure 1 (f) HRTEM image of biochar-doped g-C3N4 in Comparative Example 3 shows an amorphous or highly disordered structure with no obvious, high-resolution lattice fringes throughout the region and a uniform and dense texture.

[0102] and Figure 1 (g) TEM images of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 show that the (Ru,O)-ZIS microspheres are surrounded by a sparse network structure, which may be supported CN / C particles. Further observation... Figure 1 (h) The HRTEM image of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 shows that the lattice spacings of 0.320, 0.324, and 0.420 nm correspond to the (102) crystal plane of ZIS, the (002) crystal plane of g-C3N4, and the (006) crystal plane of ZIS, respectively, indicating that CN / C was successfully loaded on (Ru,O)-ZIS.

[0103] Figure 1(i) The elemental mapping results of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 show that Zn, In, S, Ru, O, C and N elements are uniformly distributed in the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3, proving the formation of heterojunction.

[0104] In summary, in the CN / C / ROZIS heterojunction composite photocatalyst of the present invention, CN / C was successfully loaded onto (Ru,O)-ZIS and formed a uniform spherical structure. Its lattice characteristics and elemental distribution further confirm the successful construction of the heterojunction.

[0105] Detection Example 2 The crystal structures of the CN / C / ROZIS heterojunction composite photocatalysts prepared in Examples 1-5 and the products prepared in Comparative Examples 1-3 were characterized using X-ray diffraction (XRD) in the range of 10° to 80°. The results are as follows: Figure 2 As shown.

[0106] Depend on Figure 2 As can be seen from the content, the diffraction peaks of CN / C at 12.96° and 27.46° belong to the (100) and (002) crystal planes of g-C3N4. Compared with standard g-C3N4, the peak of CN / C in the product prepared in Comparative Example 3 shifts to a higher angle, indicating that the lattice size of g-C3N4 is reduced after the introduction of biochar; The ZIS product prepared in Comparative Example 1, the (Ru,O)-ZIS product prepared in Comparative Example 2, and the CN / C / ROZIS heterojunction composite photocatalysts prepared in Examples 1-5 all exhibited characteristic diffraction peaks of ZIS, with 21.6°, 27.7°, 39.7°, 47.5°, 52.5°, and 55.6° corresponding to the (006), (102), (108), (110), (1012), and (202) crystal planes of hexagonal ZIS (PDF#72-0773). However, the characteristic diffraction peaks of the CN / C product prepared in Comparative Example 3 were masked by the main signal peak of ZIS. No Ru or RuO was observed in the XRD patterns of the CN / C / ROZIS heterojunction composite photocatalysts prepared in Examples 1-5. x The characteristic diffraction peaks are due to the low Ru doping level (theoretical mass fraction of 0.02~0.05 wt.%), which is below the detection limit of XRD. Furthermore, Ru enters the ZIS lattice by substituting In sites, rather than forming independent Ru or RuO groups. x Crystalline phase. Furthermore, no other peaks were observed, indicating high sample purity.

[0107] Detection Example 3 The functional groups of the CN / C / ROZIS heterojunction composite photocatalysts prepared in Examples 1-5 and the products prepared in Comparative Examples 1-3 were characterized using Fourier transform infrared spectroscopy (FT-IR). The results are as follows: Figure 3 As shown.

[0108] Depend on Figure 3 As can be seen from the content, the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 can achieve a photocatalyst density of 3427 cm⁻¹. -1 The peak at 2938 cm⁻¹ is caused by the stretching vibration of the -OH bond during the preparation process. -1 The peak at 1649 cm⁻¹ originates from the stretching vibration of the CH bond. -1 The peak at 1294 cm⁻¹ is attributed to the stretching vibration of the HOH, while the peak at 1294 cm⁻¹ is attributed to the stretching vibration of the HOH. -1 The absorption peak at that location is attributed to the sp in the g-C3N4 aromatic heterocycle. 2 stretching vibration of CN bond, 1116 cm -1 and 1024 cm -1 The peaks at these locations correspond to the stretching vibrations of COC (ether bonds) and CO (hydroxyl groups) on the biochar surface, respectively, demonstrating that biochar and g-C3N4 have successfully composited and formed a stable interfacial bond, while the conjugated framework structure of g-C3N4 remains intact. In the infrared spectrum of the CN / C / ROZIS heterojunction composite photocatalyst CN / C / ROZIS3 prepared in Example 3, characteristic peaks of the product CN / C prepared in Comparative Example 3 and the product (Ru,O)-ZIS prepared in Comparative Example 2 can be observed, further indicating that CN / C has been successfully loaded onto (Ru,O)-ZIS.

[0109] Detection Example 4 The photoelectrochemical tests were performed on the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 and the products prepared in Comparative Examples 1-3. The results are as follows: Figures 4-6 As shown.

[0110] Depend on Figure 4 As shown in the UV-Vis spectrum of (a), the absorption edge of the ZIS product prepared in Comparative Example 1 is relatively short, and its light response range is narrow. However, the absorption edge of the CN / C / ROZIS3 heterojunction composite photocatalyst prepared in Example 3 is significantly red-shifted, and its absorbance in the visible light region is higher than that of the (Ru,O)-ZIS product prepared in Comparative Example 2. This proves that the CN / C / ROZIS3 heterojunction composite photocatalyst prepared in Example 3 has enhanced absorption capacity for visible light.

[0111] Depend on Figure 4 As shown in the Tauc plot in (b), the E of the product ZIS prepared in Comparative Example 1 is... gThe value was 2.42 eV, and the E value of the product (Ru,O)-ZIS obtained in Comparative Example 2 was... g The value is 2.32 eV, and the E of the product CN obtained in Comparative Example 3 is... g The value is 2.58 eV. The E value of the CN / C / ROZIS heterojunction composite photocatalyst CN / C / ROZIS3 prepared in Example 3 is 2.58 eV. g The value is 2.14 eV. It can be seen that the CN / C / ROZIS heterojunction composite photocatalyst CN / C / ROZIS3 prepared in Example 3 has the smallest band gap. The smaller the band gap, the easier it is to absorb low-energy visible light. This is consistent with the UV-VIS spectral results, indicating that the composite modification has achieved band gap regulation and improved the visible light absorption capacity of the material.

[0112] The Mott-Schottky curves of the products prepared in Comparative Examples 2-3 and the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 were tested at 1500 Hz and 2000 Hz, respectively. The results are as follows. Figure 5 As shown in (a)-(c), the slopes of the products prepared in Comparative Examples 2-3 and the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 are all positive, indicating that they are all n-type semiconductors. The flat band potential of the product (Ru,O)-ZIS prepared in Comparative Example 2 is -0.50 V vs SCE, the flat band potential of the product CN / C prepared in Comparative Example 3 is -0.98 V vs SCE, and the flat band potential of the CN / C / ROZIS3 heterojunction composite photocatalyst prepared in Example 3 is -0.79 V vs SCE. According to the Nernst equation, these can be converted to -0.26, -0.74, and -0.55 V vs NHE, respectively.

[0113] Compared to the flat band potential, the valence band (VB) of an n-type semiconductor is typically shifted negatively by 0.2 V. Therefore, the VB of the product (Ru,O)-ZIS prepared in Comparative Example 2 can be calculated as -0.46 V vs NHE, the VB of the product CN / C prepared in Comparative Example 3 can be calculated as -0.94 V vs NHE, and the VB of the CN / C / ROZIS heterojunction composite photocatalyst CN / C / ROZIS3 prepared in Example 3 can be calculated as -0.75 V vs NHE. Therefore, it can be deduced that the valence band (VB) positions of the products prepared in Comparative Examples 2-3 and the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 are 1.86, 1.64, and 1.39 V vs NHE, respectively.

[0114] Depend on Figure 6(a) The PL spectra of the CN / C / ROZIS heterojunction composite photocatalyst prepared in Example 3 and the products prepared in Comparative Examples 1-3 show that, compared with the ZIS product prepared in Comparative Example 1, the (Ru,O)-ZIS product prepared in Comparative Example 2 can suppress the recombination of some photogenerated carriers, while the CN / C / ROZIS3 heterojunction composite photocatalyst prepared in Example 3 exhibits the most significant PL quenching. This indicates that the S-type heterojunction can more effectively suppress the recombination of photogenerated charges.

[0115] The sample was further tested using TRPL, and the results are as follows: Figure 6 As shown in (b), the fitting results indicate that the CN / C / ROZISS-type heterojunction composite photocatalyst CN / C / ROZIS3 prepared in Example 3 has an average carrier lifetime of 3.25 ns, significantly higher than that of pure ZIS in Comparative Example 1 (1.64 ns), (Ru,O)-ZIS in Comparative Example 2 (2.96 ns), and CN / C in Comparative Example 3 (2.45 ns). This result further demonstrates that constructing an S-type heterojunction can effectively suppress photogenerated carrier recombination and significantly extend carrier lifetime. This indicates that the S-type heterojunction provides a rapid transfer channel for photogenerated carriers, significantly reducing carrier recombination and facilitating efficient charge migration to surface active sites.

[0116] Figure 6 (c) EIS shows that the CN / C / ROZIS3 heterojunction composite photocatalyst prepared in Example 3 has the smallest radius, indicating that it has a lower charge transfer resistance and thus a faster charge transfer rate compared with the products prepared in Comparative Examples 1-3.

[0117] pass Figure 6 (d) The transient photocurrent response shows that the CN / C / ROZIS3 heterojunction composite photocatalyst prepared in Example 3 exhibits the strongest photocurrent signal, indicating that the CN / C / ROZIS3 heterojunction composite photocatalyst prepared in Example 3 has the fastest carrier migration rate and can suppress the recombination of photogenerated electron-hole pairs. Photoelectrochemical characterization consistently confirms that the S-type CN / C / ROZIS3 heterojunction significantly promotes the spatial separation and migration efficiency of photogenerated carriers by accelerating charge transfer, reducing the recombination rate of photogenerated charges, and extending carrier lifetime, thereby promoting the increase in the photocatalytic hydrogen production rate.

[0118] Case 5 Electron paramagnetic resonance (EPR) spectroscopy was used to detect the active free radicals generated during the photocatalytic water splitting to hydrogen production reaction of the CN / C / ROZIS heterojunction composite photocatalyst CN / C / ROZIS3 prepared in Example 3 and the products prepared in Comparative Examples 2-3, using DMPO as a spin trapping agent. The results are as follows: Figure 8 and Figure 9 As shown.

[0119] Figure 8 The EPR spectra (a)-(b) further confirm the charge transfer mechanism in the CN / C / ROZIS3 heterojunction composite photocatalyst prepared in Example 3. Under illumination, the product (Ru,O)-ZIS prepared in Comparative Example 2 can only generate ·O2. - The absence of a ·OH signal indicates that its conduction band electrons have strong reducing power, but its valence band hole oxidation power is insufficient; the ·OH signal of the CN / C product prepared in Comparative Example 3 is low. However, the CN / C / ROZIS3 heterojunction composite photocatalyst prepared in Example 3 not only simultaneously detected ·O2 but also showed no ·OH signal. ⁻ The CN / C / ROZIS heterojunction composite photocatalyst of this invention exhibits both ·O2 and ·OH signals, with both intensities significantly enhanced. This phenomenon indicates that an S-type heterojunction is formed at the interface between CN / C and (Ru,O)-ZIS in the CN / C / ROZIS heterojunction composite photocatalyst of this invention. Under illumination, photogenerated electrons in the conduction band of (Ru,O)-ZIS recombine with photogenerated holes in the valence band of CN / C under the drive of the built-in electric field at the interface. The strongly oxidizing holes retained in the valence band of (Ru,O)-ZIS and the strongly reducing electrons retained in the conduction band of CN / C are effectively separated and participate in the redox reaction. Therefore, the CN / C / ROZIS heterojunction composite photocatalyst CN / C / ROZIS3 prepared in Example 3 possesses both ·O2 generation and ·OH signal generation capabilities. ⁻ The ability of (electrons from the CN / C conduction band) and ·OH (holes from the (Ru,O)-ZIS valence band) confirms that the S-type heterojunction successfully retains the strong redox potentials of each component and achieves efficient space charge separation.

[0120] Figure 9 The band structure of the CN / C / ROZIS3 heterojunction composite photocatalyst prepared in Example 3 is shown. Under visible light irradiation, photogenerated electrons in the (Ru,O)-ZIS conduction band recombine with photogenerated holes in the CN / C valence band at the interface, while the strongly oxidizing holes (1.86 V) retained in the (Ru,O)-ZIS valence band and the strongly reducing electrons (-0.94 V) retained in the CN / C conduction band are effectively separated and participate in the reaction. This band structure is the theoretical basis for the efficient and stable hydrogen production achieved by the CN / C / ROZIS heterojunction composite photocatalyst of this invention.

[0121] Based on the above characterization results, a reasonable photocatalytic reaction mechanism for the S-type CN / C / ROZIS3 heterojunction is proposed, such as... Figure 10 As shown in equation (2), under sunlight, both CN / C and (Ru,O)-ZIS are excited to generate photogenerated electrons and holes.

[0122] .

[0123] Due to the differences in band structure and Fermi level between the two semiconductors, a built-in electric field is formed at the heterojunction interface, providing a driving force for the directional migration of photogenerated carriers. The conduction band (CB) and valence band (VB) positions of CN / C are -0.94 V and 1.64 V vs NHE, respectively, while those of (Ru,O)-ZIS are -0.46 V and 1.86 V vs NHE, respectively. At the heterojunction interface, photogenerated electrons in (Ru,O)-ZIS recombine with photogenerated holes in CN / C under the drive of the built-in electric field. Meanwhile, the strongly oxidizing holes retained in the valence band of (Ru,O)-ZIS and the strongly reducing electrons retained in the conduction band of CN / C are effectively separated, participating in oxidation and reduction reactions respectively, forming a typical S-type charge transfer mechanism. After migrating to the surface of (Ru,O)-ZIS, the photogenerated holes undergo an oxidation reaction with triethanolamine (TEOA). Holes in the valence band of (Ru,O)-ZIS are mainly consumed by the oxidation of TEOA, as shown in (3)-(4).

[0124] The process releases protons (H) + This provides a proton source for the subsequent hydrogen evolution reaction. EPR testing further confirmed this charge transfer mechanism, and ·O2 was simultaneously detected in CN / C / ROZIS3 under illumination. ⁻ The presence of ·OH signals indicates that the CN / C conduction band electrons (-0.94 V) have sufficient reducing power to reduce O2 to ·O2. ⁻ The (Ru,O)-ZIS valence band hole (1.86 V) can release OH... - The oxidation to ·OH directly verifies the successful construction of the S-type heterojunction. After the photogenerated electrons migrate to the CN / C conduction band, they rapidly migrate to the surface active sites through the electron transfer channel constructed at the CN / C and (Ru,O)-ZIS interface. The photogenerated electrons that migrate to the surface reduce the protons generated by water splitting and the protons released during TEOA oxidation to hydrogen gas. The hydrogen evolution reaction process is shown in Equation (5).

[0125] The overall reaction of the CN / C / ROZIS3 photocatalytic system is shown in equation (6), where TEOA oxThis indicates the oxidation product of TEOA.

[0126] In summary, this invention utilizes sugarcane bagasse-derived biochar doped with g-C3N4 (CN / C) as an electron channel, and constructs an S-type heterojunction with Ru and O co-doped ZnIn2S4 (ROZIS), developing a highly efficient visible-light photocatalytic hydrogen production system—a CN / C / ROZIS heterojunction composite photocatalyst. This invention prepares CN / C through a one-step calcination process, followed by a one-step hydrothermal in-situ recombination to obtain the target catalyst. The process is simple and achieves resource utilization of waste materials. Characterization results confirm that the introduction of CN / C effectively suppresses radiative recombination of photogenerated carriers, prolongs the effective carrier lifetime, broadens the visible light response range, optimizes the band structure, and maintains a high redox potential. The optimal sample achieves a hydrogen production rate of 9.786 mmol·g⁻¹. -1 ·h -1 It exhibits 76.3 times the activity of pure ZnIn2S4, with an apparent quantum efficiency of 19.07% at 400 nm, and retains 86.24% of its initial performance after four cycles, demonstrating both high activity and stability. This invention provides a new strategy for the synergistic modification of ZnIn2S4-based photocatalysts and has promising application prospects.

[0127] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.

[0128] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.

[0129] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.

Claims

1. A CN / C / ROZIS heterojunction composite photocatalyst, characterized in that, The CN / C / ROZIS heterojunction composite photocatalyst is composed of ruthenium- and oxygen-doped indium zinc sulfide as the main body and biochar-doped graphitic carbon nitride as the supporting phase; wherein... The CN / C / ROZIS heterojunction composite photocatalyst is spherical and has an S-type heterojunction composite structure; The biochar-doped graphitic carbon nitride in the CN / C / ROZIS heterojunction composite photocatalyst has a mass fraction of 0.02~0.50 wt.%.

2. The CN / C / ROZIS heterojunction composite photocatalyst according to claim 1, characterized in that, The ruthenium and oxygen co-doped indium zinc sulfide is self-assembled from two-dimensional nanosheets, exhibiting a three-dimensional petal-shaped spherical microstructure; Biochar-doped graphitic carbon nitride nanoparticles are dispersed and loaded on the surface and interlamellar gaps of a ruthenium- and oxygen-doped indium zinc sulfide three-dimensional petal-shaped spherical microstructure.

3. The CN / C / ROZIS heterojunction composite photocatalyst according to claim 1 or 2, characterized in that, The biochar is made from sugarcane bagasse.

4. A method for preparing a CN / C / ROZIS heterojunction composite photocatalyst as described in any one of claims 1-3, characterized in that, The preparation method includes: 1) In the presence of an alkaline solution, nitrogen-containing precursors and sugarcane bagasse are mixed, dried, and calcined to obtain biochar-doped g-C3N4, i.e. CN / C; 2) In the presence of a solvent, CN / C, zinc salt, indium salt, sulfur source, oxygen source and ruthenium salt from step 1) are mixed, subjected to hydrothermal reaction, cooled, washed and dried to obtain CN / C / ROZIS heterojunction composite photocatalyst.

5. The preparation method according to claim 4, characterized in that, In step 1), the alkaline solution is an aqueous solution of potassium hydroxide and / or an aqueous solution of sodium hydroxide; Preferably, the concentration of the alkaline solution is 2.5~10 g / L; The nitrogen-containing precursor is selected from one or more of melamine, dicyandiamide, urea, and thiourea; The mass ratio of the nitrogen-containing precursor to bagasse is 1:0.0020~0.0030.

6. The preparation method according to claim 4 or 5, characterized in that, In step 1), the mixing conditions include: ultrasonication for 0.5 to 2 hours at a power of 200 to 400 W; The drying conditions include: a temperature of 60~80℃ and a time of 8~16h; The calcination conditions include: a temperature of 500~600℃ and a time of 1~3h.

7. The preparation method according to any one of claims 4-6, characterized in that, In step 2), the solvent is deionized water and / or distilled water; The zinc salt is selected from one or more of zinc chloride, zinc acetate, and zinc acetate; The indium salt is indium trichloride and / or indium nitrate; The sulfur source is selected from one or more of thioacetamide, thiourea, and L-cysteine; The oxygen source is selected from one or more of polyvinylpyrrolidone, ethylene glycol, citric acid, and Pluronic F127; The ruthenium salt is selected from one or more of ruthenium trichloride hydrate, ruthenium acetate, and ruthenium acetylacetonate; The molar ratio of the zinc salt, indium salt, sulfur source, oxygen source, and ruthenium salt is 1:2:8:0.002~0.004:0.15~0.25; wherein the zinc salt is calculated based on the amount of zinc, the indium salt based on the amount of indium, the ruthenium salt based on the amount of ruthenium, and the oxygen source based on the molar amount of the equivalent active oxygen-containing group. The ratio of zinc salt to CN / C is 1 mmol: 0.0001~0.002 g, wherein the zinc salt is in the form of Zn. 2+ count.

8. The preparation method according to any one of claims 4-7, characterized in that, In step 2), the conditions for the hydrothermal reaction include: a temperature of 160~200℃ and a time of 12~24h; The washing conditions include washing with deionized water and anhydrous ethanol 3 to 5 times each; The drying conditions include: under vacuum conditions, at a temperature of 70~90℃, for a time of 8~16h.

9. The application of a CN / C / ROZIS heterojunction composite photocatalyst as described in any one of claims 1-3 in visible light photocatalytic water splitting for hydrogen production.

10. A method for photocatalytic water splitting to produce hydrogen, characterized in that, The method includes: dispersing the photocatalyst in a triethanolamine aqueous solution with a volume fraction of 15-25%, adding an alkaline substance to adjust the system to alkalinity, purging the air in the reaction system with an inert gas, and then carrying out a photocatalytic hydrogen production reaction under visible light irradiation. The photocatalyst is the CN / C / ROZIS heterojunction composite photocatalyst according to any one of claims 1-3; Add 80-120 mg of photocatalyst and 1-2 g of alkaline substance to every 20 mL of triethanolamine aqueous solution; The alkaline substance is sodium hydroxide and / or potassium hydroxide; The inert gas ventilation time is 20-40 min; The reaction temperature for the photocatalytic hydrogen production reaction is 15~30℃; The wavelength of the visible light satisfies λ>420 nm.